RUNX1 Upregulates CENPE to Promote Leukemic Cell Proliferation - Liu, Shan; Yang, Jianyu; Sun, Guohuan; Zhang, Yawen; Cheng, Cong; Xu, Jin; Yen, Kuangyu; Lu, Ting (Frontiers in Molecular Biosciences, 2021)
RUNX1 is a Runt family transcription factor that plays a critical role in normal hematopoiesis, including the differentiation and proliferation of hematopoietic cells. RUNX1 mutations, including chromosomal translocations, cause abnormal cell differentiation, but the mutation alone is not sufficient to cause leukemia. In MLL-fusion-induced leukemia, dysregulated wild-type RUNX1 can promote leukemia survival. Nevertheless, the underlying mechanisms of dysregulated wild-type RUNX1 in leukemia development have not been fully elucidated. This study overexpressed and knocked down RUNX1 expression in THP-1 human leukemia cells and CD34+ hematopoietic stem/progenitor cells to investigate the biological functions affected by dysregulated RUNX1. Our data indicated RUNX1 facilitated proliferation to promote leukemia cell growth. Furthermore, we demonstrated that RUNX1 knockdown in leukemia cells drastically diminished colony-forming ability. Finally, the RUNX1-knocked down cell depletion phenotype could be rescued by overexpression of CENPE, a cell proliferation gene and a RUNX1 direct target gene. Our results indicate a possible mechanism involving the RUNX1-CENPE axis on promoting leukemic cell growth.